Aplicação de ferramentas CAE/CAD e INVENTOR versão estudantil como demonstração didática no ensino da aplicação das forças nos planos horizontal e vertical para a primeira série do ensino médio. - Gil, Heleyne Karen Lima (Brasil, 2022)
The study of forces in physics is on several occasions, an obstacle for high-school students, for many of them cannot visualize its practical applicability and in everyday situations. The study of this area of dynamics is crucial not only for students who have proficiency in the exact sciences or more specifically for those who intend to go into Engineering, since these concepts always permeate our whole life. This discussion raises guiding questions such as “How to increase the ability of freshmen high-school students to understand the application of forces?”, “What can be done to demonstrate in a more comprehensive way its practical applicability to everyday life?”, "What methodology should one use to teach these students how to use computational tools for this end?" and "Despite the recognized difficulties and with the arrival of the pandemic, how can we implement these tools in hybrid and regular education?". To answer these questions, this work aims to demonstrate to students the application of forces in the three-dimensional plane using CAE / CAD tools (Computer Aided Engineering and Computer Aided Design), besides the AUTODESK – INVENTOR. All presented tools are student version, which enhances their comprehension skills over this area of Dynamics. The tools will also motivate the students to demonstrate the application and importance in everyday life as well as comparing them to conventional theoretical methodology. The aim of this work is to use this study mechanism as a tool of regular and hybrid teaching, complementary to freshmen year classes. The educational byproduct will be intended to demonstrate how to use the tools to assist teachers by applying the method in the classroom.